SPENDING REVIEW AS A POLICY TOOL FOR ENSURING EFFICIENCY IN PUBLIC EXPENDITURES AND ITS IMPACT ON FISCAL BALANCE - Nihal Selcen HANÇER (Sayıştay Dergisi)
The evolving role of the state as an economic actor, the emphasis on efficiency in public expenditures, the need to expand fiscal space, and the spendingincreasing tendencies following 2008 crisis have necessitated the development and implementation of effective policy tools in public financial management. This article examines the spending review method, a policy tool aimed at ensuring the efficient use of public resources and conducting public expenditures on a rational basis, to determine whether it contributes to enhancing the efficiency of public spending. The analysis section of the study is based on 25 OECD countries that have integrated this method into their public financial management systems, although the practices vary from country to country, and the budget balance is acknowledged as the primary indicator of fiscal balance. The study finds that there has been a favorable shift in the formerly negative impact of public spending on budget balance since the spending review approach was implemented.